Impact of Cultivars and Planting Dates on Yield of Onion Bulbs - EL-SHAFIE, M. W.; WARID, W. A. (The Libyan Journal of Agriculture, 2023)
Two promising onion cultivars, namely; Texas Yellow Grano 502 and Giza Synthetic cultivars were planted in two years at three planting dates from late September to early December. Early planting in September produced the highest yield and the largest weight per bulb. In the combined analysis, the average yield was 38.663, 22.133, and 11.692 tons per hectare and the mean bulb weight was 130.56, 74.58, and 38.27 g in the early, medium, and late planting dates, respectively. Texas Yellow Grano 502 produced a higher yield than Giza Synthetic. The average yield ranged from 27.552 to 31.530 tons/ha for the former and 17.563 to 20.007 tons/ha for the latter. The combined analysis showed that cultivar X planting date and planting date X year interactions were significant.